PLAGL1 is associated with prognosis and cell proliferation in pancreatic adenocarcinoma - Xing Liang; Zhiping Fu; Liang Tang; Minghui Zheng; Danlei Chen; Anan Liu; Ligang Shi; Linhua Yang; Chenghao Shao; Xiaoqiang Dong (BMC Gastroenterology, 2023)
Abstract Background Emerging evidence has shown the crucial roles of pleomorphic adenoma gene (PLAG) family genes in multiple cancers. However, their functions and mechanisms in pancreatic adenocarcinoma (PAAD) remain poorly understood. Methods We analyzed the expression levels of PLAG family genes in both The Cancer Genome Atlas (TCGA) database and a Gene Expression Omnibus (GEO) database, and confirmed the results in our three independent cohorts of 382 PAAD tissues and 362 adjacent nontumor pancreatic tissues. Integrated analyses were carried out to explore the function, mechanism and prognostic value of the selected PLAG family gene in PAAD patients. Results By analyzing the TCGA and GEO databases, PLAGL1 was identified to be downregulated in PAAD tissues, and its decreasing levels of both mRNA and protein were verified in our three independent PAAD cohorts. PLAGL1 expression was inversely correlated with clinicopathological factors including the Ki67+ cell rate and pathologic stage. Further GSEA of the TCGA-PAAD cohort demonstrated that multiple signaling pathways implicated in cell proliferation were enriched in the lower PLAGL1 expressing PAAD group. Moreover, we demonstrated that PLAGL1 expression was obviously negatively associated with patients’ overall survival outcome in both the TCGA-PAAD cohort and our verification cohorts. Additionally, through MTS and BrdU assays, we further demonstrated in vitro that PLAGL1 had the impact of preventing the proliferation of pancreatic cancer cells. Conclusions Our present study suggested that downregulated PLAGL1 might act as a biomarker in predicts poor prognosis and one of important factors in increasing cell proliferation in PAAD. This study provides us with a novel prognostic marker and therapeutic strategy for PAAD, which deserves further study.